1988
DOI: 10.1152/jn.1988.59.6.1639
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-sensitivity functions of W-, X-, and Y-like relay cells in the lateral geniculate nucleus of bush baby, Galago crassicaudatus

Abstract: 1. This paper represents a continuation of our effort to examine the relationship between the physiology of distinct classes of primate lateral geniculate nucleus (LGN) cells and spatial vision. The present study focuses on modeling the contrast-sensitivity functions (CSFs) of separate LGN cell classes, examining differences in the CSFs of different classes of LGN cells and comparing the results with behaviorally defined CSFs. 2. CSFs to drifting sinusoidal gratings were obtained from single LGN relay cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
68
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 0 publications
8
68
0
Order By: Relevance
“…This potential misclassification, however, does not help explain why the more sensitive (P or K) OFF neurons failed to exhibit any significant choice related activity according to the traditional choice probability measurement. More generally, all LGN cell types likely contribute to some extent to our perception of contrast (Kaplan 2013;Norton et al 1988). Therefore, the functional involvement of the M and K pathways in increment and decrement detections needs to be further investigated in detail and compared with what we have reported here for P ON and P OFF neurons.…”
Section: Choice-related Activitymentioning
confidence: 81%
See 3 more Smart Citations
“…This potential misclassification, however, does not help explain why the more sensitive (P or K) OFF neurons failed to exhibit any significant choice related activity according to the traditional choice probability measurement. More generally, all LGN cell types likely contribute to some extent to our perception of contrast (Kaplan 2013;Norton et al 1988). Therefore, the functional involvement of the M and K pathways in increment and decrement detections needs to be further investigated in detail and compared with what we have reported here for P ON and P OFF neurons.…”
Section: Choice-related Activitymentioning
confidence: 81%
“…We quantified the peak response amplitude as the highest firing rate of the neuron, z-score normalized in reference to its baseline response. We also computed a transiency index for each neuron, which was very similar to the Phasic/Tonic Index adopted in our previous studies (Irvin et al 1986;Norton and Casagrande 1982;Norton et al 1988). Here the transiency index ϭ 100 Ϫ (100 -200 ms response Ϫ spontaneous response)/(0 -100 ms response Ϫ spontaneous response) ϫ 100.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have reported that thalamocortical neurons in secondary ascending sensory pathways project their axon to layer 1 (Herkenham, 1979(Herkenham, , 1980Aumann et al, 1998;Huang and Winer, 2000;Mitchell and Cauller, 2001) and unlike those in primary sensory ascending pathways, these neurons show poor receptive fields, labile latencies, and strong dependence on modulatory inputs (Sur and Sherman, 1982;Norton et al, 1988;Diamond et al, 1992;Zhu and Lo, 1998;Ahissar et al, 2000). Surprisingly, whisker stimuli evoke robust synaptic responses in layer 1 neurons and tuft dendrites of layer 5 pyramidal neurons recorded in vivo with a latency of ϳ5-7 msec.…”
Section: Timing Of Ascending Sensory Inputs Arriving In Layermentioning
confidence: 99%